2010
DOI: 10.1645/ge-2176.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Neospora caninum Seropositivity in Sheep from the State of Alagoas, in the Northeast Region of Brazil

Abstract: The aim of this study was to identify risk factors associated with Neospora caninum seropositivity in sheep from the State of Alagoas, in the northeast region of Brazil. Twenty-six herds were selected, and blood samples were collected from 343 animals > 6-mo-old. The indirect fluorescent antibody test (IFAT) was used for serological diagnosis of N. caninum infection. Epidemiological questionnaires were applied for each herd to identify the risk factors associated with infection. Thirty-three (9.6%) animals tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
6
15
1
4
Order By: Relevance
“…The prevalence of N. caninum infection observed in this study (7%) was similar to results from other surveys conducted in Brazil (FIGLIUOLO et al, 2004;ROMANELLI et al, 2007;UENO et al, 2009;SALABERRY et al, 2010;MUNHOZ et al, 2010;FARIA et al, 2010;MACHADO et al, 2011;ANDRADE et al, 2012) and in other countries, such as China (HUI, 2008), Czech Republic (BARTOVA et al, 2009 and Spain (PANADERO et al, 2010), with reported seropositivity rates for N. caninum ranging from 8.0 to 13.91% in the sheep samples analyzed using ELISA or IFAT. An association between the prevalence of N. caninum and crossbreed animals (P=0.0249) was observed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of N. caninum infection observed in this study (7%) was similar to results from other surveys conducted in Brazil (FIGLIUOLO et al, 2004;ROMANELLI et al, 2007;UENO et al, 2009;SALABERRY et al, 2010;MUNHOZ et al, 2010;FARIA et al, 2010;MACHADO et al, 2011;ANDRADE et al, 2012) and in other countries, such as China (HUI, 2008), Czech Republic (BARTOVA et al, 2009 and Spain (PANADERO et al, 2010), with reported seropositivity rates for N. caninum ranging from 8.0 to 13.91% in the sheep samples analyzed using ELISA or IFAT. An association between the prevalence of N. caninum and crossbreed animals (P=0.0249) was observed.…”
Section: Resultssupporting
confidence: 91%
“…In 39 (42.4%) of the 92 properties assessed at least one animal was positive for N. caninum (Table 1), with prevalence rates ranging from zero to 40%, which shows the widespread occurrence of coccidiosis among animals at the Plateau of Santa Catarina. AlMajali et al (2008), Aguiar et al (2004), Figliuolo et al (2004), Soares et al (2009), Faria et al (2010 and Salaberry et al (2010) found 45.8%, 60%, 86.6%, 17.1%, 53.8% and 83.3% of the properties with animals that tested positive for N. caninum, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, regions that present high annual rainfall index, such as Rondônia state, present higher occurrence rate for N. caninum. Results of the present study could also be related to the extensive management system of the animals, evidencing the low technical level of sheep production, what is in agreement with data reported by Faria et al (2010). In addition, results can vary according to the degree of canine presence and age of the animals.…”
Section: Discussionsupporting
confidence: 92%
“…(2011) obtained 13.1% in serological surveys conducted in sheep from farms in Minas Gerais state, southeastern region, and Faria et al (2010) in Alagoas state, northeastern region, observed occurrencerate of 9.6% in sheep.…”
Section: Introductionmentioning
confidence: 97%
“…Several works have been carried out on T. gondii and N. caninum infection in pigs, goats, and sheep (Araújo Neto et al, 2008;Azevedo et al, 2010;Faria et al, 2010) from the semiarid mesoregion of northeastern Brazil, but no research was carried out to determine the status of these agents in cats. Thus, in the present study, we aimed to determine the frequency of seroreagent for T. gondii and N. caninum and possible risk factors in domiciled and stray cats in the municipality of Patos, Paraíba state.…”
Section: Introductionmentioning
confidence: 99%